2014
DOI: 10.7232/jkiie.2014.40.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Evaluation Method for a Driver's Cognitive Workload Using ECG Signal

Abstract: High cognitive workload decreases a driver's ability of judgement and response in traffic situation and could result in a traffic accident. Electrocardiography (ECG) has been used for evaluation of drivers' cognitive workload; however, individual differences in ECG response corresponding to cognitive workload have not been fully considered. The present study developed an evaluation method of individual driver's cognitive workload based on ECG data, and evaluated its usefulness through an experiment in a drivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The participants were instructed to drive (primary task) the driving simulator while performing an N-back task (secondary task). The N-back task was to recall the N step's earlier number when an experiment instructor presented a sequence of arbitrary numbers (Hong et al, 2014;Son et al, 2010).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were instructed to drive (primary task) the driving simulator while performing an N-back task (secondary task). The N-back task was to recall the N step's earlier number when an experiment instructor presented a sequence of arbitrary numbers (Hong et al, 2014;Son et al, 2010).…”
Section: Experimental Designmentioning
confidence: 99%
“…On the other hand, there is an individual variation in heart response. Many studies have reported that heart responses to tasks show significant differences between individuals (Hong et al, 2014;Lee et al, 2010;Lal and Craig, 2001). First, an effective ECG measure varies noticeably among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies mainly used EEG and ECG sensors to measure drivers' physiological responses (Hong et al, 2014;Lee et al, 2010;Rogado et al, 2009), which may cause participants' repulsion on the sensor-attached location and the restrictions on participants' actions, due to sensor attachment. The PPG and respiration sensors are considered to be more easily embodied for actual use of a car system, compared to other bio signal sensors.…”
Section: Discussionmentioning
confidence: 99%